Evaluation of nano-silica modified ECC based on ultrasonic pulse velocity and rebound hammer - Mohammed, B.S. (Bentham Science Publishers B.V., 2017)
Introdcution: Engineered cementitious composite (ECC) has gained attention among researchers due to its superior tensile properties. To improve its modulus elasticity, due to absence of coarse aggregate, nano-silica (NS) has been added to ECC mixture. Method: To facilitate the usage of the NS-ECC in the construction industry, using nondestructive tests such as rebound hammer (RH) and ultrasonic pulse velocity (UPV) to predict the compressive strength of NS-ECC is worthwhile. Twenty mixtures with two variables which are four PVA (0.5, 1, 1.5 and 2) and five NS (0, 1, 2, 3 and 4) have been proportioned, cast, cured and tested using RH, UPV and then crushed to determine the compressive strength at age of 28 days. Results and Conclusion: Response surface methodology (RSM) has been performed to develop models for predicting the compressive strength of NS-ECC utilizing results from RH and UPV. It has been established that the newly developed models are significant with values of “Prob > F” less than 0.05 and also have variance less than 0.2. Therefore, these models can be used to predict the compressive strength of NSECC using rebound hammer or/and ultra-pulse velocity. © 2017 Mohammed et al.